2018
DOI: 10.1111/febs.14396
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from B16F0 melanoma cells alter the transcriptome of cytotoxic T cells that impacts mitochondrial respiration

Abstract: Gene expression data are available in the GEO database under the accession SuperSeries number GSE102951.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…For instance, tumors secrete growth factor-, mRNA- and miRNA-containing micro-vesicles, which can be found in the blood of cancer patients and are important players in the metastatic process (reviewed in [ 47 ]). Along this line, a recent study reported that exosomes derived from B16-F10 cells are positive for mRNA and miRNA molecules, which affect the epigenetic landscape and mitochondrial respiration in cytotoxic T cells [ 75 ]. Classical effects of TMaE are related to cancer-associated cachexia, systemic inflammation, immune system suppression, and altered coagulation [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, tumors secrete growth factor-, mRNA- and miRNA-containing micro-vesicles, which can be found in the blood of cancer patients and are important players in the metastatic process (reviewed in [ 47 ]). Along this line, a recent study reported that exosomes derived from B16-F10 cells are positive for mRNA and miRNA molecules, which affect the epigenetic landscape and mitochondrial respiration in cytotoxic T cells [ 75 ]. Classical effects of TMaE are related to cancer-associated cachexia, systemic inflammation, immune system suppression, and altered coagulation [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that greater transcriptome changes in embryos treated with oEVs could be found if embryos were analyzed after a shorter period of IVC, for example after a few hours. Bland et al [42] observed changes in the T-cell transcriptome after as little as 0.5 h of exosome treatment, while other transcriptome changes were observed after 8 h of treatment. This study suggested that exosome treatment elicits a dynamic transcriptomic signature in cytotoxic T cells that becomes apparent for some clusters of genes at 0.5 h, while others needed a longer treatment period.…”
Section: Oviductal Evs Regulate Early Embryonic Development By Alterimentioning
confidence: 99%
“…Moreover, Bland et al have recently discovered an alternative mechanism of melanoma derived-Exo, which affect the epigenetic landscape and mitochondrial respiration of cytotoxic T-cells. This results in their reduced activation [34]. Studies in different types of cancer also demonstrate that tumor-derived EVs restrain the expansion and differentiation of myeloid-derived suppressor cells (MDSCs) and T-regulatory cells (Treg) [35,36] as well as reduce the cytotoxic activity of natural killer (NK) cells by down-regulating NKG2D, NKp30, NKP46, and NKG2C receptors [37].…”
Section: Role Of Exo In Melanoma Progressionmentioning
confidence: 99%